Strategi Mengajar Guru dalam Menggunakan Kurikulum Merdeka di SD Negeri Kalikepek - Vina Anistya Cahyani; Utami Wulan Tri Puji (PGSD FKIP UPR, 2023)
Change is something that is natural and will always happen, meaning that everything in life will change, including in the world of education. Independent curriculum as an effort of the Ministry of Education, Culture, Research and Technology (Kemdikbudristek). The independent curriculum began to be designed to be implemented in schools that were ready. The implementation of this independent curriculum is based on the use of technology and learning communities to share practices between teachers, students and academics. The purpose of this research is to find out the teacher's teaching strategies in implementing the independent curriculum at Kalikepek Public Elementary School. This research method uses a qualitative approach to describe the problem and research focus. The results of this study in Kalikepek Public Elementary School in implementing the independent learning curriculum, namely the implementation of the independent curriculum learning process emphasized learning, which pays attention to learning that is not the same as previous learning